Pureshare Method in Dashboard Development to Monitor Warehouse Performance at PT XYZ Using the Cost Per Case (Cpc) Perspective - Millenia Shinta Anggraeni; Harummi Sekar Amarilies (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Warehouse costs contribute about 22% of the company's total logistics costs. Thus, a warehouse manager must have comprehensive knowledge of costs and cost triggers in the warehouse to be able to minimize costs while keeping customer satisfaction. One effective way to minimize warehouse costs is by conducting the cost analysis. Although PT XYZ is one of the biggest Fast Moving Consumer Goods (FMCG) companies in Indonesia applying one of the most comprehensive Enterprise Resource Planning software, its existing warehouse management support system occupies only standard Microsoft Excel. One of its warehouses, located in West Java, is responsible for more than 147,000 pallets each day, and the warehouse manager still uses Microsoft Excel with limitations in displaying the required information, especially the information related to the Cost Per Case (CPC) in every activity. Therefore, a template or dashboard that can provide information related to CPC in the warehouse is urgently needed. Given the importance of cost monitoring in the warehouse of PT XYZ, this research aims to create a dashboard that can make it easier for companies to monitor warehouse performance from a CPC perspective. The methods used in data collection consist of several processes, namely interviews, observations, and literature studies. While analyzing the needs of dashboard creation, this research uses the PureShare method. Thus, the results are obtained in the form of a proposed warehouse dashboard that can be used by the company to conduct cost analysis by providing information related to CPC of every activity in the warehouse, where the information presented on the dashboard is in accordance with the company's needs.